A cross-species approach to disorders affecting brain and behaviour. Issue 11 (November 2018) - Devinsky, Orrin; Boesch, Jordyn; Cerda-Gonzalez, Sofia; Coffey, Barbara; Davis, Kathryn; Friedman, Daniel; Hainline, Brian; Houpt, Katherine; Lieberman, Daniel; Perry, Pamela; Prüss, Harald; Samuels, Martin; et al.
Abstract Structural and functional elements of biological systems are highly conserved across vertebrates. Many neurological and psychiatric conditions affect both humans and animals. A cross-species approach to the study of brain and behaviour can advance our understanding of human disorders via the identification of unrecognized natural models of spontaneous disorders, thus revealing novel factors that increase vulnerability or resilience, and via the assessment of potential therapies. Moreover, diagnostic and therapeutic advances in human neurology and psychiatry can often be adapted for veterinary patients. However, clinical and research collaborations between physicians and veterinarians remain limited, leaving this wealth of comparative information largely untapped. Here, we review pain, cognitive decline syndromes, epilepsy, anxiety and compulsions, autoimmune and infectious encephalitides and mismatch disorders across a range of animal species, looking for novel insights with translational potential. This comparative perspective can help generate novel hypotheses, expand and improve clinical trials and identify natural animal models of disease resistance and vulnerability. Many disorders of brain and behaviour affect human and veterinary patients. In this Perspectives, Orrin Devinsky and colleagues outline a cross-species approach to understanding neurological and psychiatric conditions, including pain, cognitive decline, epilepsy, anxiety and CNS infections, and propose that collaborations between physicians and veterinarians will generate new insights for therapy development.